Brown Adipose Tissue Rescues Bone Loss Induced by Cold Exposure - Du, Jingke; He, Zihao; Xu, Mingming; Qu, Xinhua; Cui, Junqi; Zhang, Shuangyan; Zhang, Shuhong; Li, Hanjun; Yu, Zhifeng (Frontiers in Endocrinology, 2022)
Cold temperature activates the sympathetic nervous system (SNS) to induce bone loss by altering bone remodeling. Brown adipose tissue (BAT) is influenced by the SNS in cold environments. Many studies have confirmed a positive relationship between BAT volume and bone mass, but the influence and mechanism of BAT on bone in vivo and in vitro is still unknown. Two-month-old C57/BL6j male mice were exposed to cold temperature (4℃) to induce BAT generation. BAT volume, bone remodeling and microstructure were assessed after 1 day, 14 days and 28 days of cold exposure. CTX-1, P1NP and IL-6 levels were detected in the serum by ELISA. To determine the effect of BAT on osteoclasts and osteoblasts in vitro, brown adipocyte conditional medium (BAT CM) was collected and added to the differentiation medium of bone marrow-derived macrophages (BMMs) and bone marrow mesenchymal stem cells (BMSCs). Micro-CT results showed that the bone volume fraction (BV/TV, %) significantly decreased after 14 days of exposure to cold temperature but recovered after 28 days. Double labeling and TRAP staining in vivo showed that bone remodeling was altered during cold exposure. BAT volume enlarged after 14 days of cold stimulation, and IL-6 increased. BAT CM promoted BMSC mineralization by increasing osteocalcin (Ocn), RUNX family transcription factor 2 (Runx2) and alkaline phosphatase (Alp) expression, while bone absorption was inhibited by BAT CM. In conclusion, restoration of bone volume after cold exposure may be attributed to enlarged BAT. BAT has a beneficial effect on bone mass by facilitating osteogenesis and suppressing osteoclastogenesis.